2020
DOI: 10.1002/admt.202000058
|View full text |Cite
|
Sign up to set email alerts
|

A Zero‐Power Optical, ppt‐ to ppm‐Level Toxic Gas and Vapor Sensor with Image, Text, and Analytical Capabilities

Abstract: Exposure to hazardous chemicals in the air we breathe voluntarily or during dangerous Received: ((will be filled in by the editorial staff))Revised: ((will be filled in by the editorial staff))

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Most importantly, they need to detect selectively volatile organic compounds (VOCs) and gases at low ppb to ppm (parts-per-billion/million by volume) concentrations in mixtures without interference over hundreds of others (e.g., 4800 in breath 19 or 4250 in indoor air 20 ). State-of-the-art gas sensors (e.g., chemoresistive 21 or optical 22 ) provide this sensitivity by making use of nanomaterials having high specific surface area (e.g., 5 ppb acetone at 90% relative humidity (RH) by leached nanostructured Pd/ SnO 2 23 or sub-ppb detection of Cl 2 by nanoparticle-based liquid crystal sensors 24 ). Most challenging, however, is selectivity, which can be tuned to some extent by material composition of single sensors including metastable phases, 25 solid solutions, 26 mixed oxides 27 or heterostructures with unique morphology (e.g., hollow nanofibers 28 or ordered macroporous oxides 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, they need to detect selectively volatile organic compounds (VOCs) and gases at low ppb to ppm (parts-per-billion/million by volume) concentrations in mixtures without interference over hundreds of others (e.g., 4800 in breath 19 or 4250 in indoor air 20 ). State-of-the-art gas sensors (e.g., chemoresistive 21 or optical 22 ) provide this sensitivity by making use of nanomaterials having high specific surface area (e.g., 5 ppb acetone at 90% relative humidity (RH) by leached nanostructured Pd/ SnO 2 23 or sub-ppb detection of Cl 2 by nanoparticle-based liquid crystal sensors 24 ). Most challenging, however, is selectivity, which can be tuned to some extent by material composition of single sensors including metastable phases, 25 solid solutions, 26 mixed oxides 27 or heterostructures with unique morphology (e.g., hollow nanofibers 28 or ordered macroporous oxides 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…As displayed in Figure S3, both of the reflection peak positions red-shifted with the increases of insecticide vapor pressures. The results indicate that the macroporous poly(HEMA)/poly(ETPTA) film has a dynamic range of water-based insecticide detection from 0.1 vol.% to 0.001 vol.%, which is competitive with current vapor sensing technologies [38][39][40]. Importantly, the optical response of the insecticide vapor detecting is indistinguishable from that of water vapor detection for macroporous poly(HEMA)/poly(ETPTA) film.…”
Section: Resultsmentioning
confidence: 94%
“…With the help of μ-SAXD, we obtained a 2D mapping of the Sm-A orientation with layer normal nearly perpendicular to the incident X-ray beam. We have continuously demonstrated that cells sense the anisotropy of the Sm-A LC phase nature of our LCEs, promoting orientation and alignment without external stimuli, 4,15,29,49,52,53,65 and our next steps to study cell growth and behaviour on the in situ printed filaments are ongoing.…”
Section: Liquid Crystal Elastomers As Biomaterialsmentioning
confidence: 96%
“…19–21 LCEs can also mimic vital features of endogenous tissue thus satisfying the prerequisites biocompatibility and biodegradability, mechanical properties, cell spatial growth, cell alignment, and long-term studies that are considered as tissue engineering systems. 22–24 LCs have long been used and/or incorporated into materials to create composites, ensure better processing, 25–28 introduce LC properties, create chemical sensors, 29–31 and biosensors, 32,33 soft actuators, 34–38 light driven motors, 39,40 as responsive building blocks for guiding 2D cell growth, 41,42 promoters of cell orientational order, 43–45 or to control the dynamics of bacteria. 46,47…”
Section: Liquid Crystal Elastomers As Biomaterialsmentioning
confidence: 99%